2019
DOI: 10.3390/cells9010045
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Protein HOXB13 Enhances Methylmercury Toxicity by Inducing Oncostatin M and Promoting Its Binding to TNFR3 in Cultured Cells

Abstract: Homeobox protein B13 (HOXB13), a transcription factor, is related to methylmercury toxicity; however, the downstream factors involved in enhancing methylmercury toxicity remain unknown. We performed microarray analysis to search for downstream factors whose expression is induced by methylmercury via HOXB13 in human embryonic kidney cells (HEK293), which are useful model cells for analyzing molecular mechanisms. Methylmercury induced the expression of oncostatin M (OSM), a cytokine of the interleukin-6 family, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The effects of Hg have been studied in multiple cell lines and animal models [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]; however, evidence regarding primary cells remains scarce. To address this research gap within the context of female reproduction, the extent of Hg-induced damage on endometrial cells' viability and function using primary cultures of human endometrial cells were investigated in this research.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of Hg have been studied in multiple cell lines and animal models [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]; however, evidence regarding primary cells remains scarce. To address this research gap within the context of female reproduction, the extent of Hg-induced damage on endometrial cells' viability and function using primary cultures of human endometrial cells were investigated in this research.…”
Section: Discussionmentioning
confidence: 99%
“…We first examined OSGIN1 gene expression under conditions of exposure to methylmercury at a concentration that is minimally cytotoxic to C17.2 cells. Further, the concentrations and times of methylmercury exposure were based on the results of previous studies [13,15,16] and preliminary experiments to evaluate methylmercury-induced apoptosis (Figure S1). As a result, exposure to methylmercury at a final concentration of 6 µM increased OSGIN1 mRNA levels, with the maximum peak in particular being observed after 8 h of exposure (Figure 1A).…”
Section: Methylmercury Induces Osgin1 Expression In C172 Cellsmentioning
confidence: 99%
“…We comprehensively searched for intracellular factors involved in methylmercury toxicity using various search tools, and identified tumor necrosis factor α [12], homeobox B13 [13], and other factors involved in enhancing methylmercury toxicity. In contrast, we also reported that chemokine ligand 3 [14], ornithine decarboxylase 1 (ODC1) [15,16], transcription factor 3 [17], and other factors are involved in reducing methylmercury toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…More than 60 years have passed since the discovery of Minamata disease after a large population was afflicted with the disease after ingestion of large amounts of methylmercury (Al-Ardhi and Al-Ani, 2008;Sheehan et al, 2014), but the mechanisms involved in its toxicity remain unclear. We have previously reported that there are many proteins involved in methylmercury toxicity and that the intracellular levels of some of them are regulated by the ubiquitin-proteasome (UP) system (Hwang et al, 2002;Lee et al, 2020;Toyama et al, 2021Toyama et al, , 2020. Therefore, the UP system might play an important role in determining the sensitivity of cells to methylmercury toxicity.…”
Section: Introductionmentioning
confidence: 99%